'Accumulation by appropriation': The integration of recyclable-waste collector cooperatives in Salvador, Brazil, and the right to the city. (August 2022) - Manzi, Maya; Santana, Joilson Santos; Marchi, Cristina Maria Dacach Fernandez
This paper analyzes the intersection between waste, value, and the right to the city within the context of the Municipal Recycling Collection Program in Salvador, Brazil. It shows how the legal recognition of recyclable-waste collectors as legitimate workers and their integration into municipal practices of waste management has not materialized into improved working conditions and has done nothing to advance their struggle for the right to the city. A critical value perspective on this specific case demonstrates that waste and "humans-as-waste" "switching" from not-value to value-in-the-making does not represent a way of escaping abjection and exploitation. Instead, the inclusion of cooperative collectors into the municipal recycling collection program has resulted in new forms of dispossession, through state-increased control over recyclables and in the municipality appropriating the value produced by the struggles, knowledge, and informal collective labor of the collectors. The right to the city for waste workers in Salvador therefore entails the right to work with dignity and the re-appropriation of waste as the urban commons to create livelihoods based on labor relations and regimes of value against and beyond capitalism.